A Assessoria de análise e cálculos judiciais e os fatores determinantes da economia no pagamento de precatórios do Estado do Ceará - Pinho, Maria Gorete de Oliveira Catunda (2011)
This work discusses issues related to the efficiency of the state of Ceará, for the payment of precatory. Emphasizes the creation of the Advisory Judicial Calculations and Analysis-aacj and its contribution to the economy of Ceará State in relation to pay in lawsuits against the Exchequer. Presents the arguments that have caused the creation of the working group which later evolved into such Consulting focusing on the main goal: to subsidize the defense of the State Attorney, concerning the preparation of calculations to dispel doubts about the amounts due, dealing with demands more applicants which are: Economic Plans, Floor Wage, Salary Parity, Review Board, Expropriation, Compensation, Misuse of Repetition, which includes extracurricular, Additional Income and unwarranted collection of Social Security. This paper aims to demonstrate the important work of saving aacj for judicially, its contribution in reducing the amounts charged in different processes, identifying and quantifying these favorable differences achieved by the Office of calculations, allowing the state to turn expenses payments writ on investment. Having also aimed at publicizing the work done through the results achieved, contributing as an effective, ensuring a proper defense and bringing positive results to the State of Ceará sucumbente when the lawsuits. It analyzes the favorable decisions in the period 2007 to 2010. Considers a sample space of 20% (twenty percent) of these processes. From there, it uses statistical methods to consolidate the results and econometric model to explain and identify the contribution of the factors involved in the economy writ of the state of Ceara.